2021
DOI: 10.3390/environments8110112
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Contamination Survey of Environmental Fresh and Saltwater Resources of Upolu Island, Samoa

Abstract: Analysis of microbe diversity in freshwater resources and nearshore seawater samples of Upolu Island was performed to investigate the distribution of harmful bacteria. For this, 124 samples were collected from 23 river systems, two volcanic lakes, and 45 locations inside and outside the barrier reef of Upolu Island, Samoa. Physicochemical parameters for general water quality, detection of coliform bacteria and 16S rRNA amplicon sequencing were performed on all samples. Fecal indicator bacteria (FIB) testing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…A recent study that was carried out in Samoa (Upolu Island) showed the presence of many bacterial species, e.g., coliforms, etc. contaminating the water sources [52]. Another study on total coliforms and fecal coliforms was conducted in Mexico and showed the adverse effects on human communities [53].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study that was carried out in Samoa (Upolu Island) showed the presence of many bacterial species, e.g., coliforms, etc. contaminating the water sources [52]. Another study on total coliforms and fecal coliforms was conducted in Mexico and showed the adverse effects on human communities [53].…”
Section: Discussionmentioning
confidence: 99%
“…Estuarine water quality and benthic conditions are deteriorating worldwide because of urbanization and climate change [1,2]. Of particular concern are increases in the detection of pathogens in estuary waters and sediments that threaten human and ecosystem health [3][4][5][6][7]. These increases are likely due, in part, to improved detection methods.…”
Section: Introductionmentioning
confidence: 99%
“…It includes six studies carried out in different countries around the world, which focus on different aspects related to the monitoring and management of inland waters. Specifically, Ochsenkühn et al [1] investigated the presence and distribution of harmful bacteria in river, lake, and nearshore sea-water samples of Upolu Island (Samoa) by combining the sensitivity of fecal indicator bacteria testing and next-generation sequencing. A thorough genetic screening of the broodstocks used for the reintroduction of beluga sturgeon (Huso huso L.) in the Po River basin (Italy) was performed by Antognazza et al [2] to assess the success of a captive breeding program.…”
mentioning
confidence: 99%
“…The results presented in this Special Issue should be taken into account for improving both the monitoring and management of freshwater resources: (i) the wide distribution of potential harmful bacteria from river runoff or direct sewage dumping has an impact on human health that should be urgently reduced [1], (ii) a critical requirement for the success of programs for the reintroduction of locally extinct species is the knowledge of the genetic diversity of the selected broodstocks to ensure self-sustainability of the reintroduced populations [2], (iii) taxon richness of benthic macroinvertebrates could be used as a surrogate indicator to assess the water quality when consolidate biomonitoring methods are not available [3], (iv) the presence of endangered diatomic species of particular conservational interest in temporary basins affected by extended drought periods triggers the need for conservation strategies for vulnerable and unstable environments strongly threatened by climate changes [4], (v) long-term monitoring of ecosystem metabolism is required to assess alterations in the function of streams affected by hydrological and temperature alterations exacerbated by the climate change [5], (vi) common operative tools should be implemented for ecological flow assessment in order to make water resource management more sustainable [6], (vii) organic farming and biocontrol could be an alternative to diffuse pollution by agrochemicals, while environmental flows and controlled sediment flushing operations could limit the hydropower impact on rivers [8]. Moreover, the review by Salmaso et al [7] could support the proper design of monitoring plans aimed at assessing the ecological impacts of hydropeaking and the effects of possible mitigation strategies.…”
mentioning
confidence: 99%